Muslim elite responses to government's policies of modernisation in three Southern border provinces of Thailand - Nipon Sohheng (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2008)
This study examines the responses of Muslim elite to governments’ policies of modernisation in three southern border provinces of Thailand since 1932-2006. It explains the natures and characteristics of policies of modernisation in three main aspects (i.e. socio-political, socio-economic and educational). It assesses the roles and responses of Muslim elite towards governments’ policies of modernisation. Finally, it examines the approaches to the solution adopted by Muslim elite to interact with the Thai governments. The theoretical framework of this study’s analysis is based on the Imitative Foreign Solution, Imitative Historical Solution and Islamic Asalah Solution pioneered by Abdul Hamid A. AbuSulayman. The orientation of this study employs two methods of data collection, which are interviews and documentary consultation. The unstructured interview is used and both primary and secondary data are searched. The findings of this study show that, firstly, many of governments’ policies towards Muslims, in certain degree, do not really satisfy the Muslim elites of different classifications in this study especially the forced assimilation policy and the policy in the area of economic development, though some governments’ policies do meet their satisfaction with a request of few reformulations like the policy for the establishment of Islamic higher educational institution. Second, Muslim elites’ responses to the socio-political policies are rather negative especially the policy of forced assimilation, central political appointment, and conflict resolution. Third, Muslim elites’ responses to the socio-economic policies are also negative, especially the issue concerning riba (interest-based transaction). Fourth, Muslim elites’ responses to the educational policies are somewhat satisfactory. Particular pleasure of Muslim elites is on the policy for the establishment of Islamic higher educational institution. Fifth, most of Muslim elites’ reactions and suggestions employ Islamic asalah solution in dealing with the Thai governments’ policies towards Muslims.